THE METALLOGRAPHIC ANALYSIS OF STEEL OF H12MF TYPE AFTER TEMPERING BY LASER EMISSION - M. L. Kalinichenko; V. A. Kalinichenko; S. V. Grigoryev; M. A. Kardapolova (Литьë и металлургия)
The article is related to the processes of laser processing. The purpose of work was to optimize technological parameters of the process which would reduce internal tensions in forged piece and would improve quality of surface. The analysis of distribution of elements shows their rather uniform distribution in surface coating. The achieved results have practical importance for optimization of technological parameters and choice of optimal structure and as result of properties